COVID-19 and tuberculosis: the double whammy of respiratory pathogens. (13th April 2022) - Shariq, Mohd; Sheikh, Javaid A.; Quadir, Neha; Sharma, Neha; Hasnain, Seyed E.; Ehtesham, Nasreen Z.
Prior to coronavirus disease 2019 (COVID-19), tuberculosis (TB) was the worst killer among infectious diseases. The union of these two obnoxious respiratory diseases can be devastating, with severe public health implications. The COVID-19 pandemic has affected all TB-elimination programmes due to the severe burden on healthcare systems and the diversion of funds and attention towards controlling the pandemic. The emerging data show that the COVID-19 pandemic caused a marked decrease in case notifications and bacille Calmette–Guérin immunisations, ultimately promoting disease transmission and increasing the susceptible population. The similarity between the clinical characteristics of TB and COVID-19 adds to the public health complications, with evidence of immune dysregulation in both cases leading to severe consequences. Clinical evidence suggests that severe acute respiratory syndrome coronavirus 2 infection predisposes patients to TB infection or may lead to reactivation of latent disease. Similarly, underlying TB disease can worsen COVID-19. Treatment options are limited in COVID-19; therefore, using immunosuppressive and immunomodulatory regimens that can modulate the concomitant bacterial infection and interaction with anti-TB drugs requires caution. Thus, considering the synergistic impact of these two respiratory diseases, it is crucial to manage both diseases to combat the syndemic of TB and COVID-19. M. tuberculosis is a deadly human pathogen, and the emergence of COVID-19 has hampered TB control measures. Better co-infection management can prevent disease-related complications and produce favourable outcomes. https://bit.ly/3LiiV57